2018
DOI: 10.2334/josnusd.17-0317
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective clinical study of 296 patients with mass lesions of the tongue

Abstract: To better understand the clinical features of mass lesions of the tongue, we retrospectively evaluated frequency, recurrence rate, and complications in 296 patients who had undergone surgery for such lesions. The diagnoses were fibroma (43.6%), mucous cyst (14.2%), papilloma (11.8%), hemangioma (7.8%), granuloma (6.4%), lipoma (1.4%), schwannoma (1.0%), ectopic tonsil (0.7%), and other (13.2%). Recurrence was noted in two patients (0.7%). Twentytwo patients (7.4%) developed surgical complications, including li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
4
5
0
4
Order By: Relevance
“…Clinical differential diagnosis of oral lipoma must be performed with other benign tumours, mainly fibromas or fibroepithelial hyperplasias, salivary neoplasms, schwannoma, neurofibroma, etc However, it can also be found in the parotid gland and intraosseous regions, mimicking cysts …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical differential diagnosis of oral lipoma must be performed with other benign tumours, mainly fibromas or fibroepithelial hyperplasias, salivary neoplasms, schwannoma, neurofibroma, etc However, it can also be found in the parotid gland and intraosseous regions, mimicking cysts …”
Section: Discussionmentioning
confidence: 99%
“…with other benign tumours, mainly fibromas or fibroepithelial hyperplasias, salivary neoplasms, schwannoma, neurofibroma, etc 10,15 However, it can also be found in the parotid gland and intraosseous regions, mimicking cysts. 16 In our series, 8.2% of the cases occurred in the palate, which according to the literature is a rare location, 17 and almost 16% of them were on the tongue.…”
Section: Clinical Differential Diagnosis Of Oral Lipoma Must Be Perfomentioning
confidence: 99%
See 2 more Smart Citations
“…by Aittiwarapoj et al, 23 Shamloo et al, 24 Gambino et al, 27 and Miyake et al 28 . Ion Ciucă Mărăşescu et al 29 reported that two-thirds of carcinoma of the tongue developed in the mobile part of the tongue, especially the margins.…”
Section: Discussionmentioning
confidence: 96%